Prevalence of vitamin D deficiency and its relationship with metabolic syndrome markers and lifestyle in the adult population in a sunny tropical region - Hossein Safari; Mohammad Hassan Eftekhari; Jafar Hassan Zadeh; Arash Dashtabi (Shiraz University of Medical Sciences, 2017)
Background:Serum vitamin D (VIT D) concentration has been inversely associated with the prevalence of metabolic syndrome (MS), but the relationship has remained unclear. We evaluated the prevalence of VIT D deficiency, and its association with MS, and its components in the adult population in a sunny tropical region (Lamerd: a city in the south of Iran)Patients and Methods: Totally, 210 patients referring to different medical centers across the Lamerd city participated in this cross-sectional study through January and February of 2016. To select medical service center, we used a one-stage cluster sampling method. Anthropometric indices and dietary intake were measured using modified food frequency questionnaire (FFQ) and blood samples collected. Data were analyzed using SPPS version 16, Pearson's correlation was used to investigate the bivariate relationships between the variables, and unpaired t-test was used to determine the differences between genders for all variables. A P-value < 0.05 was considered statistically significant.Results:Overall, 62 menand 144 womenwith a mean age of 35.84± 10.84 years old completed this study; the prevalence of VIT D deficiency among the participants equaled 64.1% (women=66.7% and men=58.1%). A significant positive relationship between sun exposure time on the serum VIT (p= <0.0015), and a negative relationship between the serum VIT D on triglyceride (p= 0.035), TC (p= 0.025, age (p= 0.001), and fasting blood sugar (p= <0.001) were found.Conclusions: This study showed that lower VIT D concentrations were associated with increased MS risk factors.